Five Models of Spiritual Direction in the Early Church. By George E. Demacopoulos - Young, Frances M. 1939- (2010)
The subject matter of this book is the pastoral oversight exercised by the bishop, and the increasing influence of the monastic model on episcopal practice in the fourth to sixth centuries. The five models discussed are Athanasius, Gregory Nazianzen, Augustine, Cassian, and Pope Gregory I, each representing a different response to the ascetic pattern. It is necessary to explain this, as it is hardly clear from the book’s title, given that ‘spiritual direction’ is now defined as ‘the process of accompanying people on a spiritual journey’, the focus being on ‘spiritual experiences’ (quoted from the website of Spiritual Directors International).
Keywords: Rezension